2019
DOI: 10.4028/www.scientific.net/kem.822.834
|View full text |Cite
|
Sign up to set email alerts
|

Fusible Glass Based on Glassy Chalcogenide Type Systems Ge-S(Se)Br, Ge-S(Se)I

Abstract: Theoretical and practical results on the preparation and investigation of low-melting glasses using the example of glassy chalcogenide glasses of the Ge-S-Br, Ge-Se-Br systems are presented and summarized. On the basis of fundamental properties of matter, correlations were identified with uniform positions. The glass formation regularities in the indicated chalcogenide and oxyhalide systems were determined. Areas and compositions of low-melting chalcogenide and oxyhalide glasses were considered. Approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, since limited knowledge of the Ge-S-Br glass system, there is no generally accepted agreement on the presence of structural fragments in Ge-S-Br glasses. Some authors concluded the Ge-S-Br glasses with a polymer network that consists of GeS 4/2 and S chains linked by bonds and dissolved GeBr 4 molecules [11]. On the other hand, Ge-S-Br glasses were investigated by Raman spectra, which were hypothesized with mixed tetrahedra GeS 4-n Br n formed in Ge-S-Br glasses [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, since limited knowledge of the Ge-S-Br glass system, there is no generally accepted agreement on the presence of structural fragments in Ge-S-Br glasses. Some authors concluded the Ge-S-Br glasses with a polymer network that consists of GeS 4/2 and S chains linked by bonds and dissolved GeBr 4 molecules [11]. On the other hand, Ge-S-Br glasses were investigated by Raman spectra, which were hypothesized with mixed tetrahedra GeS 4-n Br n formed in Ge-S-Br glasses [12].…”
Section: Introductionmentioning
confidence: 99%